Linking Climate Change Adaptation Strategies and Nutrition Outcomes: A Conceptual Framework. Issue 2 (June 2022) - Macheka, Lesley; Mudiwa, Tatenda; Chopera, Prosper; Nyamwanza, Admire; Jacobs, Peter
Background: The relationship between climate adaptation strategies and nutrition security is poorly understood and often unclear. Although several adaptation strategies have been implemented to mitigate the impact of climate change, there is still a lack of conclusive evidence or studies on the interrelationships between adopted climate change adaptation strategies and nutrition outcomes. Objective: This study aimed to develop a conceptual framework that links climate change, adaptation strategies and nutrition and to show the indicators that can be used to assess the impact of climate adaptation strategies on nutrition. Methodology: The proposed conceptual framework was developed through a literature review. Results: A generic conceptual framework that could be used to assess the impact of adopted climate change adaptation strategies on nutrition outcomes was developed. The framework consists of 5 key elements: agro-food system, context characteristics, adaptation strategies, climatic shocks and stress, and system output. The principles used in designing the conceptual framework include systems approach, contingency theory, and system output. Conclusion: The developed framework offers a channel to evaluate adopted climate change adaptation strategies and their impact on nutrition outcomes. Such a conceptual framework can also be used in selecting and identifying more suitable climate adaptation strategies given specific contextual environments.